Management of sport injuries with Korean medicine: A survey of Korean national volleyball team - Yang, C.; Lee, E.; Hwang, E.-H.; Kwon, O.; Lee, J.-H. (Evidence-Based Complementary and Alternative Medicine, 2016)
The purpose of this study was to report the current state of Korean medicine (KM) treatment on sports injury by implementing survey with volleyball team medical doctors participating in 2013-2014 season. Six KM doctors completed a questionnaire that includes injury parameters: type, location, situation, and pain scores. We collected 166 injury cases from 94 Korean male and female national volleyball players. Knee (25.9%), low back (13.3%), elbow, and ankle (8.4%) injuries were most common. Joint (41.6%) and muscle (30.7%) were major injured tissues. KM team medical doctors utilized acupuncture (40.4%), chuna manual therapy (16.0%), physical therapy (15.2%), taping (9.0%), and cupping (7.8%) to treat volleyball injuries. Any types of medications were used infrequently. Additional physical and exercise therapy were preferred after receiving acupuncture (both 46.9%). This study presented the preliminary injury profile of Korean elite volleyball players. Injury and treatment parameters could be useful to build advanced KM model in sport medicine.